The impact of six sigma on human capital management : a case study of 3M Ireland - Eng, Poo Jiuan (2008)
The case study focuses on 3M Ireland and how the new corporate Six Sigma initiative impacts its local Human Capital Management (HCM) model and Human Resource (HR) practices.